Axial claw pole motor: harmonic torque estimation using finite element method. Issue 5 (10th July 2020) - Giraud, Dominique; Ristagno, Baptiste; Netter, Denis; Fontchastagner, Julien; Labbe, Nicolas; Lanfranchi, Vincent
Abstract : Purpose: This paper aims to propose a method to evaluate the information obtained on harmonics calculations and to estimate the precision of results using finite element method for an innovative motor topology in which some well-known meshing rules are difficult to apply. Design/methodology/approach: The same magnetostatic problem is solved with several mesh sizes using both scalar and vector potentials magnetics formulations on a complex topology, an axial claw pole motor (ACPM). The proposed method lies in a comparison between the two weak formulations to determine what information is obtained on harmonics calculations and to estimate its precision. Moreover, an original mesh method is applied in the air gap to improve the numerical results. Findings: The precision on harmonics calculations using finite element method on an ACPM is estimated. For the proposed motor and mesh, only the mean value (even with large mesh) and the first harmonic (with fine mesh) of torque are calculated with a good accuracy. This results confirm that the non-respect of the meshing rules have a strong impact on the results and that scalar and vector potentials magnetics formulations do not give exactly the same results. Before using torque harmonics values in vibration calculations, a finite element model has to be validated by using both fomulations. Research limitations/implications: This method is time-consuming and only applied on an ACPM in this work. Originality/value: The axial claw pole motor, for which the classic meshing rules cannot be applied, is a complex topology very under-studied. To improve the calculation of space harmonics, the authors proposed to split the airgap into four parts. Then in the two central parts, the meshing step of the structured mesh is equal to the rotating step.